Decision Support System for Prioritizing Economic Sectors for Regional Investment Using AHP-TOPSIS - Nurmaliana Pohan; Pradani Ayu Widya Purnama; Nurfa Rahma Julita; Hana Afifah (Ali Institute or Research and Publication, 2026)
The volatility of quarterly Gross Regional Domestic Product (GRDP) growth across economic sectors poses a significant challenge for regional governments in determining investment priorities. This study develops a decision support system (DSS) to rank investment priorities among economic sectors in West Sumatra Province using a hybrid Analytic Hierarchy Process–Technique for Order Preference by Similarity to Ideal Solution (AHP-TOPSIS) method. Five criteria were extracted from three dimensions of GRDP growth rates, namely C-to-C, Q-to-Q, and Y-on-Y, for 2024–2025: average C-to-C growth, average Y-on-Y growth, Q-to-Q stability (the inverse of standard deviation), latest quarter growth (Q4 2025), and positive consistency (the number of quarters with growth > 0). Criteria weights were determined through an AHP pairwise comparison questionnaire completed by regional economic experts, resulting in a consistency ratio (CR) of 0.015. The TOPSIS method was then applied to rank 17 economic sectors. The results show that the top five investment priorities are Government Administration, Defense, and Mandatory Social Security (O) = 0.711; Health Services and Social Activities (Q) = 0.671; Financial Services and Insurance (K) = 0.633; Other Services (R) = 0.594; and Real Estate (L) = 0.573. The system was implemented as an interactive dashboard using Python Streamlit. The ranking results are consistent with regional development conditions, as validated by experts. This DSS provides an objective, data-driven tool for regional investment policymaking.